Aplicação de programação linear na seleção de carteiras de investimento - Siervo, Juliano Squarsone Di (2017)
It is shown in this dissertation the applicability of Harry M. Markowitz´s Modern Theory, allied to Operation Research, in the diversification of actions in an investment portfolio, minimizing its total risk in a given expected feedback. So, Linear Programming is used in order to model the portfolio´s variance, and the Simplex Method to determine the optimized portfolio. In a second step, Quadract Programming is used in order to model the portfolio´s variance and the model is implemented in the software MATLAB. Based on the results, their relevance an advantages are discussed.